How to evaluate the effect of pain treatments in cancer patients: Results from a longitudinal outcomes and endpoint Italian cohort study. (5th December 2012) - Corli, O.; Montanari, M.; Greco, M.T.; Brunelli, C.; Kaasa, S.; Caraceni, A.; Apolone, G.
Abstract Background Dealing with cancer pain implies assessing the intensity and other attributes of pain and identifying appropriate outcomes and endpoints to evaluate the effect of treatments. Methods In the context of an observational longitudinal prospective study, 1461 painful cancer patients were evaluated at baseline and weekly over 4 weeks. Four pain intensity (PI) measures (worst, average, least and right now: WP, AP, LP, and PRN), pain relief and patients' satisfaction with pain treatments were recorded. Starting from these data, we extrapolated the full responder (FR) subjects, whose PI decreased by ≥2 points, or by ≥30%, or who obtained a final score of ≤5 points, according to criteria previously suggested by literature. The receiver operating characteristics (ROC) curve analysis was used to estimate the predictive accuracy. Results All the PI measures decreased from the initial to final visit: the reduction was 1.9 as WP, 1.3, 0.8 and 1.2 as AP, LP and PRN, respectively. The proportion of FR differed from 47.8% to 88.3% depending on PI measures and the criterion adopted. ROC analysis showed an acceptable accuracy of all endpoints and confirmed the cut‐offs recommended by the literature. The best criterion corresponded to a PI absolute value of ≤4 points when measured as AP. Conclusions All measures applied seem able to profile the evolution of pain, with some differences. This implies the need of an appropriate choice of outcomes and endpoints according to the goal and objective of the intervention under evaluation.